Impairment of Quality of Life among Patients with Wearable Cardioverter Defibrillator Therapy (LifeVest®): A Preliminary Study. (27th June 2018) - Lackermair, Korbinian; Schuhmann, Christoph G.; Kubieniec, Michaela; Riesinger, Lisa M.; Klier, Ina; Stocker, Thomas J.; Kääb, Stefan; Estner, Heidi L.; Fichtner, Stephanie
Abstract : Background . Wearable cardioverter defibrillator (WCD) therapy is feasible and safe in patients as a transient protection against sudden cardiac death (SCD). However, the impact of WCD therapy on quality of life (QoL) has not been studied. Methods . In our single-centre study, 109 consecutive patients with a prescription of WCD were retrospectively analysed. Quality of life has been assessed by a standardized questionnaire (EQ-5D-3L, modified). Additionally, clinical baseline and follow-up data and recorded arrhythmic episodes were evaluated. Results. Mean WCD therapy time was 56.2 (± 42.4) days, with a daily wear time of 19.7 (± 5) hours. A total of 3441 arrhythmia episodes were detected. Of these, 27 (1%) were adequate but did not require shock therapy. Likewise, no inadequate shock therapy occurred. WCD therapy negatively affected quality of life: 43% of patients reported mental health issues. 37% reported pain or discomfort. Self-care, usual activities, and mobility were restricted in 17%, 48%, and 36%, respectively. 29% were afraid of receiving shock therapy, and 48% suffered from sleep disturbance. However, 64% indicated having felt safe during WCD therapy. Accordingly, average quality of life was rated 70/100 points. Conclusion. In our cohort, no SCD was prevented by WCD therapy. In contrast, in this preliminary study quality of life was reduced. Thus, careful recommendation of WCD therapy for high risk patients should be considered.